The Effect of a Moodle-Based LMS in “Article Writing for Journal” Subject for Post Graduate Students - Tomo Tomo; J. Priyanto Widodo; Shierly Novalita Yappi (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The goal of this study was to find out how effective a Moodle-based Learning Management Systems (LMS) work for post-graduate students at STKIP PGRI Sidoarjo who are taking a “Article Writing for Journal” subject. To reach that goal, we used total sampling in an experimental method with a pre-test and post-test design for two groups. The students who took part in the study were post-graduate students in the third semester of the 2020/2021 academic year. There were two groups, and each group had 12 students in it. The researchers gave the students a pre-test and a post-test about “Article Writing” as the products to get the data. Then, the researcher used a t-test to see if the model had an effect on the data. The students who were taught using a Blended method that used LMS Moodle and those who were only taught in a virtual class were both better at writing than those who were only taught in a virtual class. SPSS version 26 was used to look at data from the pre- and post-tests. The Manova test and the Normalized gain were used to look at the data (N-gain). Manova's results showed that there was a significant difference in how well students learned to write in English. This means that the treatment that included Moodle-based e-learning and only face-to-face classes has had a big impact on students’ English writing skills.